How barefoot and conventional shoes affect the foot and gait characteristics in toddlers - Gimunová, Marta; Kolářová, Kateřina; Vodička, Tomáš; Bozděch, Michal; Zvonař, Martin (PloS one, 2022)
OBJECTIVES: Barefoot shoes have recently become a popular alternative to conventional shoes among the parents of pre-school children. As the long-term effect of habitual shoe-wearing on the foot is still unclear, the aim of this study was to compare the arch index, dynamic foot anthropometry and gait parameters in toddlers who had been habitually wearing barefoot shoes or conventional shoes since their first steps. METHODS: 30 toddlers- 15 habitually wearing barefoot shoes (BF group) and 15 habitually wearing conventional shoes (N-BF group)-participated in this study. Each child was measured twice during the study. The first data collection session occurred within one month after the first five consecutive unsupported steps were performed by the toddler. The second data collection session occurred seven months after this event. At each data collection session, the toddler was instructed to walk barefooted at its natural speed over an Emed® platform (Novel GmbH, Germany). The Emed ® software generated data regarding the arch index, dynamic foot anthropometry, foot progression angle, contact area, contact time, peak pressure and maximum force. The Wilcoxon signed-rank test was used to compare the differences between the 1st and 2nd data collections. The Mann-Whitney U test was used to compare the differences between the BF and N-BF groups. RESULTS: The results of this study show a higher plantar arch and a smaller foot progression angle in the BF group. The forefoot width in both the BF and N-BF groups remained proportional to the foot length after seven months of independent walking. CONCLUSIONS: These findings may encourage parents and caregivers to introduce barefoot shoes or create a habitual barefoot time for their child.
Keywords: Child; obuv; Gait; Foot; Walking; chůze; předškolní dítě; chůze (způsob); biomechanika; Humans; Shoes; lidé; Biomechanical Phenomena; noha (od hlezna dolů); Child, Preschool; dítě